1998
DOI: 10.1097/00004872-199816121-00010
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized low-density lipoprotein increases the production of intracellular reactive oxygen species in endothelial cells

Abstract: ox-LDL increased the intracellular formation of ROS through the ligation to a specific endothelial receptor. Preincubation of HUVECs with lacidipine, a calcium antagonist with antioxidant properties, significantly reduced the intracellular ROS formation induced by ox-LDL. We propose that the effect of lacidipine on adhesion molecule expression and on NF-kB activation can be explained by its effect on intracellular ROS formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 39 publications
6
44
0
2
Order By: Relevance
“…31,32 Antioxidant activity has also been reported for other CCBs, 26,33,34 including lacidipine, a compound with which activity was observed in preclinical models of atherosclerotic disease, as well as in hypertensive patients, in whom a beneficial effect on carotid intima-media thickness and number of plaques was demonstrated.…”
Section: Antioxidant Properties Of Ccbsmentioning
confidence: 89%
“…31,32 Antioxidant activity has also been reported for other CCBs, 26,33,34 including lacidipine, a compound with which activity was observed in preclinical models of atherosclerotic disease, as well as in hypertensive patients, in whom a beneficial effect on carotid intima-media thickness and number of plaques was demonstrated.…”
Section: Antioxidant Properties Of Ccbsmentioning
confidence: 89%
“…It has been reported that patients with acromegaly have increased plasma concentrations of cholesterol [22], lipoprotein (a) and small dense LDL [23,24], and patients with hypercholesterolemia have impaired endothelium-dependent vasodilatation [25,26]. In fact, it has been shown that oxidized LDL-C impairs NO production [27], which plays a key role in the development of endothelial dysfunction and atherosclerosis [28] by production of reactive oxygen species [29].…”
Section: Discussionmentioning
confidence: 99%
“…Samples were washed twice with PBS containing bovine serum albumin and analyzed with 10,000 cells/sample in flow cytometry (Coulter). The binding of di-15-ASP-labeled ox-LDL was expressed as mean fluorescence intensity (MFI) as described previously (37), and the data were fitted with GraFit (38). In our conditions, after incubation with ox-LDL, cell viability was always greater than 95%.…”
Section: Specific Binding Of Labeled Ox-ldl To Baecs and Blox-1-cho Cmentioning
confidence: 99%